Critical Ecological Medical Anthropology of Rural Transformation in Izmir-Ali̇ağa-Horozgedi̇ği̇ Village - Gözde Dalan Polat (Journal of Economy Culture and Society)
Before 1970, inhabitants of Horozgediği Village in Aliağa, used to make their living from vine growing, olive, tobacco, cotton and wheat farming, horticulture and animal husbandry but after Aliağa was declared to be an industrial site, the village started to industrialize in the early 1970’s. The village was surrounded by iron and steel factories and was subject to rural transformation. Following the transformation of agricultural areas into industrial sites after the 1970’s, a health migration is now taking place in the village due to the resulting heavy air pollution and the diseases and health problems considered to be related to this. The air pollution caused by the industry has disrupted the whole ecological balance of the village. All living creatures from vegetation to animals have become sick and cancer has started to be frequently mentioned in the village (Sofuoğlu, Baytak, Bayram, Müezzinoğlu, Odabaşı, Seyfioğlu, Elbirve Tuncel, 2008). These frequently experienced health problems in the village have caused households to migrate slowly over time. The problems created by this rural transformation have been interpreted through the works of social scientists such as Zerzan (2009), Güvenç (2016, 2010, 2008), Latour (2008), Beck (2011), which are considered to be covered by critical ecological health anthropology (Young, 2002). In this study, the participant observation technique for anthropology was used. Unstructured in-depth interviews were conducted with the inhabitants of the village and people who have migrated from the village, doctors from various departments of Public Health who had previously carried out research in the village, environmental and cultural platforms, and also journalists. The research findings have been published under headings such as “Like Hell: Air Pollution and Its Effects on Health”, “Health Migration: Karanfil/Carnation Street” and “ From Bağ-Bahçe to Industry, from Farming to Nakliyecilik. As a result, the people of this region, which was expected to develop economically under the name of development, are instead more impoverished and their health has been adversely affected.